Historical-Analysis Role of Early Christian Missionaries in Promoting Education in Nigeria - Moses Adeleke ADEOYE (Higher Education Spiritual Pedagogies, 2023)
This historical examination explores the significant contribution that early Christian missionaries made to the advancement of education in Nigeria. This study sheds light on the historical significance of these missionaries' contributions by thoroughly examining their arrival, activities, impact on education, and long-term impacts on Nigerian society. The foundation of missionary schools, the creation of curricula and teaching strategies, and the promotion of literacy and numeracy are all topics covered in the article. It examines the problems and issues surrounding missionary education, such as assimilation concerns and cultural conflicts. The study also looks into the legacy of Christian missionaries' labour and their contributions to education. This research contributes to a deeper knowledge of the history of education in Nigeria and the larger implications for educational development in post-colonial contexts by looking at historical sources and engaging in critical analysis.